Spatial distribution of hospital admissions diabetes mellitus in Espírito Santo state, Brazil (Brazilian Journal of Health Research, 2021)
Introduction:Diabetes melittus is a metabolic disease featured by hyperglycemia; it is associated with kidney and heart complications that increase the likelihood of diabetes-associated hospitalization by two to six times. Objective: Analyzing the spatial distribution of hospital admissions due to diabetes mellitus in Espírito Santo State, from 2011 to 2015. Method: Ecological study about diabetes-associated hospitalization of adult individuals living in different counties in Espírito Santo State was carried out from 2011 to 2015. Hospitalizations were featured based on absolute and relative frequencies. Subsequently, hospitalization rates were calculated and smoothed by global and local Bayesian estimators. Local Moran’s Index was used to check local spatial correlation. Results: In total, 11,514 hospitalizations due to diabetes mellitus were reported in Espírito Santo State, from 2011 to 2015; The highest prevalence of hospitalizations was observed among 60-year-old (or older), brown and female individuals, - with a significant number of patients required emergency care. Iuna and São Roque do Canaã were the counties recording the highest and lowest gross rates, respectively. After the Moran Global smoothing and local methods were applied, it was possible seeing that Irupi County and Vitória City presented the highest and the lowest diabetes-associated hospitalization rates, respectively. Conclusion: Based on the spatial analysis, it was possible identifying the counties in need tof expanding, structuring or improving their primary health - care services to enable specific planning focusing on reducing the number of hospitalizations due to diabetes.
Keywords: Diabetes Mellitus; Hospitalization; Descriptive Epidemiology; Spatial Analysis